COMPARISON OF FRESH SERUM TOTAL CHOLESTEROL RESULTS WITH THOSE OF SERUM STORED AT ROOM TEMPERATURE FOR 6 HOURS AT JATI PADANG GENERAL HOSPITAL - Sari, Anis Sinta; Yanti, Ni Ketut Ayu Mira; Yanti, Ni Luh Gede Puspita (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Exposure to X-ray radiation in conventional radiology procedures can pose a health risk, especially for accompanying caregivers of pediatric patients who only bear the risk without gaining any benefit. This study aims to determine the estimated equivalent dose received by accompanying caregivers of pediatric patients and the safest points during conventional radiology examinations. The method used in this research is a field survey, involving the measurement of equivalent radiation doses inside and outside the examination room using a personal dosimeter, as well as measuring the radiation dose rate at 6 points using a surveymeter. The data was processed to obtain the highest and lowest values, as well as the percentage of equivalent dose obtained compared to the established Dose Limit Value (DLV). The results showed that the highest radiation dose received by accompanying caregivers inside the examination room reached 13,46 µSv, with a percentage of 0,27% relative to the DLV, while the lowest dose recorded was 1,12 µSv, with a percentage of 0,0224% relative to the DLV. Analysis of the radiation dose rate distribution revealed that the greater the distance of the measurement point from the radiation source (tube), the smaller the dose received. In conclusion, the radiation dose received by accompanying caregivers is still below the Dose Limit Value (DLV) for caregivers, which is 5.000 µSv. However, to minimize stochastic effects, the implementation of additional protective measures, such as the use of lead aprons and selecting safer locations within the examination room, is highly recommended. These findings are expected to serve as a guide in enhancing the safety of accompanying caregivers of pediatric patients in conventional radiology units.